1977
DOI: 10.1007/bf01315627
|View full text |Cite
|
Sign up to set email alerts
|

Serological relationships between rotaviruses from different species as studied by complement fixation and neutralization

Abstract: Human, piglet, mouse, foal, lamb, calf and rabbit rotaviruses all infected, but could not readily be subcultured in LLC MK2 cells. Cells infected with mouse and calf rotaviruses reacted by indirect immunofluorescence (FA) with convalescent serum from children, piglets, mice, foals, lambs, calves or rabbits, taken after rotavirus infection. Human, calf, piglet, mouse and foal rotaviruses reacted with human, calf, mouse, foal and lamb convalescent serum by complement fixation (CF). It was not possible to disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
76
2
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(82 citation statements)
references
References 21 publications
3
76
2
1
Order By: Relevance
“…The results obtained indicated that antiserum prepared against the Lincoln strain of bovine rotavirus showed various neutralization patterns for the isolates, and these results were different from those of the CF test considered to be related with common "group antigen" of rotaviruses (5,10,12). They suggest that there may be serotypes in bovine rotaviruses by the SN test, as in human and avian rotaviruses (2,5,11,13).…”
contrasting
confidence: 38%
“…The results obtained indicated that antiserum prepared against the Lincoln strain of bovine rotavirus showed various neutralization patterns for the isolates, and these results were different from those of the CF test considered to be related with common "group antigen" of rotaviruses (5,10,12). They suggest that there may be serotypes in bovine rotaviruses by the SN test, as in human and avian rotaviruses (2,5,11,13).…”
contrasting
confidence: 38%
“…similar morphology (Flewett, Bryden & Davies, 1973;McNulty, 1978) and clinical signs (Flewett & Woode, 1978), share a common group specific antigen (Woode et al 1976; Thouless et al 1977), cross protection (Gaul et al 1982) and inter-species transmissions (Tzipore & Makin, 1978;Dagenais et al 1981). However, despite these findings which indicate that not all rotaviruses are species-specific, there is no direct evidence of rotavirus infection between animal species and man as a zoonosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several subgroups Greenberg et al 1983) and serotypes (Beards et al 1980;Wyatt et al 1982) have been identified by complement fixation tests (Thouless et al 1977;Zissis & Lambert, 1978), ELISA techniques (Yolken et al 1978;Thouless, Beards & Flewett, 1982) and neutralization assays (Beards et al 1980;Wyatt et al 1982).…”
Section: Introductionmentioning
confidence: 99%